Забезпечення сталого розвитку підприємства як основа формування соціальної відповідальності - Гальчак, Х. Р. (Видавництво Львівської політехніки, 2016)
Узагальнено основні теоретичні положення і визначено особливості процесу формування соціальної відповідальності в контексті забезпечення сталого розвитку підприємства. Виділено принципи стратегії сталого розвитку, що стали ключовими у формуванні концепції соціальної відповідальності. Запропоновано концептуальну схему забезпечення сталого розвитку підприємства як основи побудови соціальної відповідальності. The article summarizes the basic theoretical concepts and the formation process peculiarities of social responsibility in the context of sustainable company development. Author raised the issue of building a common platform for dialogue between government, business and society, where social responsibility is the key factor. He considered scientific approaches to defining the concept’s essence of social responsibility which equals to values, because they are the basis of culture and benchmarks for enterprise activity and development. The role and place of social responsibility in a system of sustainable development is also revealed. In particular, the concept of corporate social responsibility as a system of scientifically based ideas, principles and provisions was presented. As well as its role in achieving sustainable development is justified. During the research of sustainable development strategy in general, the author focuses on the concept of corporate stability. This concept is described as a management model, which includes following three aspects: economic, social and environmental. Author reveals features of the sustainable development strategy principles, which became key-points in shaping the social responsibility concept. Importance of investment for sustainable enterprise development is noted in this article. It was proved, that development of sustainable economic is impossible without the active participation of the government in regulating innovative investment support for companies, that are actively engaged in the implementation of environmental and social programs that make up the socio-economic value to the development of civil society. A conceptual scheme for sustainable enterprise development process was proposed, as a foundation for the social responsibility growth. Also, corporate governance features of global companies are covered in current work, main “landmark” of which is the concept of sustainable development, and the main tool – the social responsibility. The article emphasizes the main risks during the integration of strategy for sustainable development in Ukraine, as well as business philosophy of Ukrainian companies. The problems and prospects of building corporate social responsibility in Ukraine are described in this work, on the principles of sustainable development. It is proved that an effective mechanism for the formation of social responsibility in Ukraine is possible only in case of adequate implementation of relations, principles and values of the corporate sustainability concept.
Ensuring sustainable development of an enterprise as a prerequisite for social responsibility
Keywords: концепція сталого розвитку; корпоративна соціальна відповідальність; принципи; гуманність; екологізація виробництва; sustainable development concept; corporate social responsibility; principles; humanity; greening production